PEMANFAATAN TEKNOLOGI DI BIDANG PENDIDIKAN DASAR MELALUI PENDAMPINGAN MASYARAKAT DI DESA KOLELET PADA ERA PANDEMI COVID-19 - Ipah Ema Jumiati; Maulana Adi Firmansyah; Mia Nur Ajizah; Made Ari Handayani; Surya Surya (Setia Mengabdi: Jurnal Pengabdian kepada Masyarakat, 2022)
Since the rise of the covid-19 spread in the late Chinese city of wuhan last year, it has caused coronavirus to spread to the 200 remaining countries in the world. The first covid-19 growth in Indonesia in March 2020 has seen an increase in covid-19 cases. The cumulative impact of this pandemic has impeded some areas of socio-economic, health, and educational activity from Indonesia. At this time of the pandemic, even technology could be harnessed to the utmost advantage in education. The positive effects of technology can make it easier for any community from urban to rural communities to experience the same educational system. However, the negative effects of technology can also result in something bad if its use is not used wisely. In this pandemic, education is felt among the people of kolelet village where the barrier of online study at colelet village remains a problem ranging from the lack of awareness of the use of technology for learning and the use of intelligent and correct technologies. This is where my friends and I encouraged the community of kolelet village in the field of education through the university university student's employment program ageng tirtayasa.